PENGARUH DEFORMASI DINGIN, ANNEALING, SMAT, SERTA SANDBLASTING TERHADAP STRUKTUR MIKRO, KEKERASAN, DAN LAJU KOROSI BAJA TAHAN KARAT 316L - , MIRZA PRAMUDIA, Dr. Suyitno, S.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Austenitic 316L stainless steel is the metal that most widely used in biomaterial applications. Austenitic 316L stainless steel has some advantages such as resistance to the corrosive environment, good formability, biocompatible, and good fatigue resistance. Besides has some advantages, austenitic 316L stainless steel also has disadvantages, such as low strength and wear resistance, prone to crevice corrosion, pitting corrosion, as well as stress corrosion resistance (SCC), limited surface modification technique that can be applied without removing the material advantages. Several methods were used to improve the weakness of austenitic 316L stainless steel such as cold working which is the totally mechanical treatment method. This research aim to study the effect of cold deformation, annealing, SMAT, and sandblasting on microstructure, microhardness, and the corrosion rate of austenitic 316L stainless steel. Cold deformation is the specimen thickness reduction process with the emphasis in room temperature. Specimens were pressed by using hydraulic press machine with 27 % degree of deformation which conducted twice processes and each process was followed by annealing process. Specimen resulted were processed further with sandblasting and SMAT. Sandblasted specimens were prepared by the manufacturer by using silica sand with 0.5 to 0.8 mm of diameter and 6-7 kg/cm2 of compressor pressure for 10 minutes. SMAT specimens were prepared by using 250 pieces of steel balls for 15 minutes. The results of this study conclude that hardness and corrosion resistance increases with increasing degree of deformation. The annealing process does not affect on hardness of AISI 316L specimens. Sandblasting and SMAT process result in grain refinement and increase the hardness on the sample surface.